PUBLIC SERVICE DELIVERY IN INDONESIA’S OUTER ISLANDS: A PERFORMANCE EVALUATION - Ponto, Iriane Sosiawaty; Waisapy, Jeanly; Fadli, Zul (JPAP: Jurnal Penelitian Administrasi Publik, 2025)
This study evaluates the performance of Civil State Apparatus personnel in delivering public services in Kairatu Barat Sub-district, West Seram Regency, a remote archipelagic region in Eastern Indonesia. Using a sequential explanatory mixed-methods design, the research involved 94 respondents comprising 37 Civil State Apparatus staff and 57 community service recipients. Data collection employed structured questionnaires and in-depth interviews to obtain comprehensive perspectives on public service quality. Findings reveal that Civil State Apparatus performance is generally categorized as good, with work precision emerging as the primary strength (score: 3.92). However, significant weaknesses exist in service innovation (score: 3.51). From the community perspective, staff friendliness received the highest appreciation (score: 3.88), reflecting the internalization of local cultural values of "Pela Gandong." Conversely, procedural simplicity obtained the lowest rating (3.44), particularly in licensing services. Correlation analysis revealed that staff friendliness has the strongest relationship with community satisfaction (r=0.734), confirming the importance of relational aspects in public service delivery within Maluku’s cultural context. Competency and work motivation are the most influential internal factors affecting performance, while limited technological infrastructure constitutes the primary external constraint. The study identifies significant intergenerational digital divides and geographic variations in service usage patterns. Key policy recommendations include: (1) implementing simple communication technology aligned with infrastructure capacity; (2) streamlining service procedures to reduce citizen burden, especially for island communities; (3) strengthening Civil State Apparatus reward systems to sustain motivation; and (4) developing differentiated service strategies that leverage cultural capital while accommodating diverse community needs. These findings provide actionable guidance for improving public service delivery in archipelagic governance contexts.